1983
DOI: 10.1017/s0003356100001690
|View full text |Cite
|
Sign up to set email alerts
|

Physiological attributes as possible selection criteria for milk production 3. Plasma hormone concentrations and metabolite and hormonal responses to changes in energy equilibrium

Abstract: 1983). Physiological attributes as possible selection criteria for milk production 3. Plasma hormone concentrations and metabolite and hormonal responses to changes in energy equilibrium. Request Permissions : Click here Downloaded from http://journals.cambridge.org/ASC, IP address: 205.175.97.198 on 05 Apr 2015 Arum. Prod. litf. J7: 165-178 (*K)3-.V6l/83/23010165$()2'H0 ABSTRACT Plasma hormone concentrations and metabolite responses to changes in energy equilibrium were measured in experiments designed to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…This elevated blood glucose of HBI animals is consistent with previous studies of the Massey University selection lines (Flux et al, 1984;Xing et al, 1988;Xing, 1989). It is, however, important to note that while differences with respect to circulating insulin have been obtained consistently with the Massey University selection lines, they have not been observed with other dairy cattle selection lines (Land, Carr, Hart, Osmond, Thompson and Tilakaratne, 1983;Serjsen et al, 1984;Barnes, Kazmer, Akers and Pearson, 1985;Sinnett-Smith et al, 1987). Alternatively, the greater basal glucose levels in the HBI calves may have arisen from a decreased glucose utilization by peripheral tissues.…”
Section: Discussionmentioning
confidence: 85%
“…This elevated blood glucose of HBI animals is consistent with previous studies of the Massey University selection lines (Flux et al, 1984;Xing et al, 1988;Xing, 1989). It is, however, important to note that while differences with respect to circulating insulin have been obtained consistently with the Massey University selection lines, they have not been observed with other dairy cattle selection lines (Land, Carr, Hart, Osmond, Thompson and Tilakaratne, 1983;Serjsen et al, 1984;Barnes, Kazmer, Akers and Pearson, 1985;Sinnett-Smith et al, 1987). Alternatively, the greater basal glucose levels in the HBI calves may have arisen from a decreased glucose utilization by peripheral tissues.…”
Section: Discussionmentioning
confidence: 85%
“…Il est cependant possible que les races ou les individus à fort potentiel laitier présentent, à bilans nutritionnels comparables, des taux de somatotropine endogène plus élevés, bien que les données existantes soient peu nombreuses et contradictoires (Hart, 1983 ;Land et al, 1983 ;Truscott et al, 1983 ;Flux et al, 1984 ;Barnes et al, 1985 ;Lukes et al, 1987 ; Oyler, 1987 , et plus récemment avec des formes « retard » de la somatotropine recombinée.…”
unclassified
“…Blood components are related to fertility, growth and body composition in cattle (Blum et al 1983; Land et al 1983;Rowlands et al 1983). Selection experiments designed to change some blood components in poultry (McClung et al 1972) and mice (Tilakaratne et al 198 I ; Yamaki and Mizuma 1982) have been successful.…”
mentioning
confidence: 99%
“…Comparison of blood composition in different biological types of dairy cattle (Tilakaratne et al 1980;Land et al 1983; Roy et al 1983;Flux et al I 984), and dairy and beef crossbreds (Blum et al 1983) have been reported. Correlated changes of blood composition in pigs selected for growth rate and reduced backfat have also been examined (Bakke and Tveit 1977; Mersmann et al 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation